A Qualitative Study of Living in a Healthy Food Priority Area in One Seattle, WA, Neighborhood - Jenny L. Wool (MDPI AG, 2021)
Policy makers in several major cities have used quantitative data about local food environments to identify neighborhoods with inadequate access to healthy food. We conducted qualitative interviews with residents of a healthy food priority area to assess whether residents’ perceptions of food access were consistent with previous quantitative findings, and to better understand lived experience of food access. We found that proximity to stores, transportation mode, and cost shaped decisions about food shopping. The local food bank played an important role in improving food access. Participants had varied suggestions for ways to improve the neighborhood, both related and unrelated to the food environment.